2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of white matter anisotropy in modeling electroconvulsive therapy

Abstract: White matter in the brain exhibits strong anisotropic conductivity. Modeling studies on electroencephalography have found that such anisotropic conductivity greatly influences the estimated dipole source. In this study, we made a detailed comparison of the effects of conductivity anisotropy using a computational model of electroconvulsive therapy (ECT). The human head model was a high resolution finite element model generated from MRI scans, implemented with tissue heterogeneity and an excitable neural model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Computational modelling of the tDCS stimulus has indeed suggested that white matter anisotropy is highly related to the distribution of the tDCS electric field, particularly in subcortical regions (Bai et al, 2011;Suh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Computational modelling of the tDCS stimulus has indeed suggested that white matter anisotropy is highly related to the distribution of the tDCS electric field, particularly in subcortical regions (Bai et al, 2011;Suh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%